The complex interactions between obesity, metabolism and the brain - Uranga, Romina Maria (2019)
Obesity is increasing at unprecedented levels globally, and the overall impact ofobesity on the various organ systems of the body is only beginning to be fullyappreciated. Because of the myriad of direct and indirect effects of obesity causingdysfunction of multiple tissues and organs, it is likely that there will be heterogeneityin the presentation of obesity effects in any given population. Taken together, theserealities make it increasingly difficult to understand the complex interplay betweenobesity effects on different organs, including the brain. The focus of this review isto provide a comprehensive view of metabolic disturbances present in obesity, theirdirect and indirect effects on the different organ systems of the body, and to discussthe interaction of these effects in the context of brain aging and the development ofneurodegenerative diseases.